TECHNOLOGY OF OPEN-ENDED ENGINEERING IN TRAINING OF ENGINEERS - A. P. ISAEV; L. V. PLOTNIKOV; N. I. FOMIN (Высшее образование в России, 2017)
The article presents the authors’ technology of interdisciplinary open-ended engineering. This technology is an integrated teaching method that significantly increases the practical component in the educational program. It creates conditions to overcome the shortcomings in engineering education. The basic ideas of the technology of open-ended engineering, the experience of their implementation in higher education and the authors’ vision of teaching technology are examined in the article. The paper highlights the main stages of development process of the technology of open-ended engineering to prepare students in higher school of engineering (Ural Federal University). As well as the complex of methodological tools and procedures. The presented organizational model of open-ended engineering technology integrates the functions of creation and implementation of all educational program. The authors analyze the characteristics of students’ educational activity while implementing projects according to the technology of open-ended engineering and present the intermediate results of the application of the authors’ technology in engineering education process of the undergraduate engineering students.